2023
DOI: 10.3389/fmed.2023.1105854
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning reveals sex differences in clinical features of acute exacerbation of chronic obstructive pulmonary disease: A multicenter cross-sectional study

Abstract: IntroductionIntrinsically, chronic obstructive pulmonary disease (COPD) is a highly heterogonous disease. Several sex differences in COPD, such as risk factors and prevalence, were identified. However, sex differences in clinical features of acute exacerbation chronic obstructive pulmonary disease (AECOPD) were not well explored. Machine learning showed a promising role in medical practice, including diagnosis prediction and classification. Then, sex differences in clinical manifestations of AECOPD were explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Clinical variables, including advanced age, male sex, the absence of overweight, and dyspnea, were predictors of airflow obstruction. [29][30][31][32] In our analysis, elderly, lower BMI and respiratory symptoms showed negative effect on pulmonary function and sPAP in male smokers, which was in line with previous studies. We found that the earlysmoking group had a higher possibility of developing ≥two respiratory symptoms with advanced GOLD stages.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical variables, including advanced age, male sex, the absence of overweight, and dyspnea, were predictors of airflow obstruction. [29][30][31][32] In our analysis, elderly, lower BMI and respiratory symptoms showed negative effect on pulmonary function and sPAP in male smokers, which was in line with previous studies. We found that the earlysmoking group had a higher possibility of developing ≥two respiratory symptoms with advanced GOLD stages.…”
Section: Discussionsupporting
confidence: 92%